Reconfigurable optical interconnection system supporting concurrent application-specific parallel computing - Agelis, S.; Jonsson, M. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
Application specific architectures are highly desirable in embedded parallel computing systems at the same time as designers strive for using one embedded parallel computing platform for several applications. If this can be achieved, the cost can be decreased in comparison to using several different embedded parallel computing systems. This paper presents a novel approach of running several high-performance applications concurrently on one single parallel computing system. By using a reconfigurable backplane interconnection system, the applications can be run efficiently with high network flexibility since the interconnect network can be adapted to fit the application that is being processed for the moment. More precisely, this paper investigates how the space time adaptive processing (STAP) radar algorithm and the stripmap synthetic aperture radar (SAR) algorithm can be mapped on a multi-cluster processing system with a reconfigurable optical interconnection system realized by a micro-optical-electrical mechanical system (MOEMS) crossbars. The paper describes the reconfigurable platform, the two algorithms and how they individually can be mapped on the targeted multiprocessor system. It is also described how these two applications can be mapped simultaneously on the optical reconfigurable platform. Implications and requirements on communication bandwidth and processor performance in different critical points of the two applications are presented. The results of the analysis show that an implementation is feasible with today's MOEMS technology, and that the two applications can be successfully run in a time-sharing scheme, both at the processing side and at the access for interconnection bandwidth.